The Return Difference between Before and After Issuance of Sharia Bonds (Sukuk) - Wiranda, Sindi (International Journal of Business, Management and Economics, 2020)
This study aims to analyze sharia downloading which returns shares on the Indonesian Stock Exchange. This study uses a study program to see the average abnormal returns around the sharia promulgation date (sukuk) and the average difference in abnormal returns before and after sharia withdrawal (sukuk). The population in this study were all sharia negotiations published in the 2014-2019 period. and still published in February 2020. The window period is 60 days (t - 30 and t + 30) with a sample of 15 publication events. The method used in this study was the t test and Wilcoxon signed rank test. The results showed that there was an average significant abnormal return around the date of promulgation of sharia (sukuk), namely on the 29th and 1st days before the promulgation of sharia (sukuk). And the results of the Wilcoxon sign rank test show that the significance level is 0.003, which means that H0 is accepted so that there is a significant difference in average returns between before and after the announcement of the sharia withdrawal (sukuk) announcement.